Effect of soil bunds on runoff, soil and nutrient losses, and crop yield in the central highlands of Ethiopia - Adimassu, Zenebe; Mekonnen, Kindu; Yirga, C.; Kessler, A. (Wiley, 2014)
The effects of soil bunds on runoff, losses of soil and nutrients, and crop yield are rarely documented in the Central Highlands of Ethiopia. A field experiment was set up consisting of three treatments: (i) barley-cultivated land protected with graded soil bunds (Sb); (ii) fallow land (F); and (iii) barley-cultivated land without soil bund (Bc). For 3 years (2007–2009), the effect of soil bunds on runoff, losses of soil and nutrients, and crop productivity was studied. Daily runoff and soil and nutrient losses were measured for each treatment using standard procedures while barley yield was recorded from the cultivated plots. The results showed that Sb brought about significant reduction in runoff and soil losses. Plots with Sb reduced the average annual runoff by 28 per cent and the average annual soil loss by 47 per cent. Consequently, Sb reduced losses of soil nutrients and organic carbon. However, the absolute losses were still high. This implies the need for supplementing Sb with biological and agronomic land management measures to further control soil erosion. Despite these positive impacts on soil quality, Sb do not increase crop yield. Calculated on a per-hectare basis, Sb even reduce crop yield by about 7 per cent as compared with control plots, which is entirely explained by the reduction of the cultivable area by 8•6 per cent due to the soil bunds. Suitable measures are needed to compensate the yield losses caused by the construction of soil bunds, which would convince farmers to construct these land management measures that have long-term beneficial effects on erosion control.